Importance of Dendrobium officinale in improving the adverse effects of high-fat diet on mice associated with intestinal contents microbiota - Li, Xiaoya; Deng, Na; Zheng, Tao; Qiao, Bo; Peng, Maijiao; Xiao, Nenqun; Tan, Zhoujin (Frontiers in Nutrition, 2022)
A growing body of evidence suggests that the disturbance of intestinal microbiota induced by high-fat diet is the main factor causing many diseases. Dendrobium officinale (DO), a medicinal and edible homologous Chinese herbal medicine, plays essential roles in regulating intestinal microbiota. However, the extent of DO on the intestinal contents microbiota in mice fed with high-fat diet still remains unclear. Therefore, this study explored the role of intestinal contents microbiota in the regulation of adverse effects caused by high-fat diet by DO from the perspective of intestinal microecology. Twenty-four mice were randomly distributed into normal saline-treated basal diet (bcn), normal saline-treated high-fat diet (bmn), 2.37 g ·kg−1 ·days−1 DO traditional decoction-treated high-fat diet (bdn) and 1.19 g ·kg−1 ·days−1 lipid-lowering decoction-treated high-fat diet (bjn) groups for 40 days. Subsequently, we assessed the changes of body weight, serum total cholesterol (TC), total triacylglycerol (TG), low density lipoprotein-cholesterol (LDL-C), high density lipoprotein-cholesterol (HDL-C) levels and the characteristics of intestinal contents microbiota. Results demonstrated that DO exerted the modulating effect on the changes of body weight, TG, TC, LDL-C and HDL-C levels. Besides, DO decreased the richness and diversity of intestinal contents microbiota, and altered the structure as a whole. Dominant bacteria Ruminococcus and Oscillospira varied significantly and statistically. Moreover, DO influenced the carbohydrate, amino acid and energy metabolic functions. Furthermore, Ruminococcus and Oscillospira presented varying degrees of inhibition/promotion of TG, TC, LDL-C and HDL-C. Consequently, we hypothesized that Ruminococcus and Oscillospira, as the main dominant bacteria, played the key roles in the treatment of diseases associated with a high-fat diet by DO.